Development of Local Culture - Based Arts Education: Study of Buton Woven Fabric Motifs - Samparadja, Nurmala; Jayadi, Karta; Husain, Muh. Saleh (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This study aims to document and analyze the form of woven fabric motifs produced in Sula'a Weaving Village, with the goal of contributing to the development of local culture-based art education. The study uses a qualitative descriptive approach with direct observation methods, in-depth interviews, and visual documentation. The analysis technique involves data reduction, data presentation in narrative and visualization forms, and drawing conclusions based on field findings. The study's findings show that geometric patterns and plant and animal patterns on woven fabrics have meanings that are related to tradition and social class. These meanings are aesthetic, educational, and symbolic. Motifs such as horizontal lines and checkered patterns reflect harmony, loyalty, responsibility, and relationships with nature. This research also found that traditional patterns have changed over time to use geometric ideas like shifting, mirroring, and rotation to make them look better without losing the original culture's features. It also suggests ways to bring back traditions by using these patterns in the creative and tourism industries. The study's findings show that woven fabrics should be kept as a cultural heritage and that people should value local cultural goods more, even as they become more modern. This can help with the growth of arts education that is based on local culture. In addition, the results of this study can be a medium for learning, local wisdom, and character building of students in schools.